Water Use Efficiency in a Furrow System - Lee, Teang Shui; Balla, H. O. (Universiti Putra Malaysia Press, 1996)
An existing volumetric balance approach in conjunction with the Kostiakov infiltration equation for determining soil infiltration parameters in a furrow is used to study furrow irrigation in the local environment. Other parameters required include furrow geometry, assumed subsurface profile and flow advance data. A set of adjacent furrows is used to indicate the performance of the field system. The procedure outlined here can be used to evaluate efficiency of continuous mode furrow irrigation. The spatial and temporal variation of infiltration characteristics of a soil are well known. As such, the performance of a furrow irrigation system which uses the soil as a medium of conveyance varies with the ever-changing infiltration behaviour. There is therefore a need for an evaluation procedure to determine water use efficiency which can be followed throughout the irrigation season so as to enable the irrigator to make any necessary changes to improve its performance. This determination of irrigation performance hinges very much on the correct evaluation of the infiltration process, in this case, in dynamic infiltration water flowing overland in small channels. An evaluation example is given.